Dendritic core derived unimolecular micelles with poly(lactic acid) arms: Synthesis and application as a phase transfer agent. (23rd January 2022) - Shikha; Jacob, Josemon
Abstract: Unimolecular micelles refer to amphiphilic hyperbranched molecules, which exhibit micellar characteristics in a single molecule. In the present study, starting with pentaerythritol, three new dendrimers D1, D2, and D3 were synthesized in good yields bearing 9, 12, and 18 peripheral hydroxyl groups, respectively, using alkyne‐azide Husigen 1, 3‐dipolar cycloaddition reaction. The structural integrity and purity of the dendrimers were confirmed by 1 H and 13 C NMR spectroscopy, and FE‐SEM studies established their near‐spherical morphology. Using D2 as a macroinitiator, hyperbranched 12‐arm star polymers were synthesized via ring‐opening polymerization of l ‐lactide. The star polymer is found to be an efficient sequestering agent for water‐soluble dyes like congo red, bromophenol blue, and methyl orange from aqueous phase due to its amphiphilic nature demonstrating the application of unimolecular micelles in dye removal from aqueous waste.